The Performance Analysis of SIKITO LLDIKTI Region II System using COBIT 2019 Framework: A Case Study - Wulandari, Intan Fitriana; Herdiansyah, Muhammad Izman; Kunang, Yesi Novaria; Cholil, Widya; Ariandi, Muhamad; Ependi, Usman (Universitas Dharma Wacana, 2023)
In today's organizational landscape, information technology plays a critical role in supporting ongoing activities. Therefore, it is essential to conduct an analysis to determine the advantages and disadvantages of IT implementation. This research focuses on the Higher Education Service Institute (LLDIKTI) Region II, a government agency responsible for improving the quality of higher education in its working area. LLDIKTI Region II uses an information technology system that aligns with the Institute's vision and mission. However, the governance level of the Online Functional Position Information System known as SIKITO has never been assessed, highlighting the need for a maturity framework to measure SIKITO's level and align it with LLDIKTI's vision and mission goals. COBIT 2019 is a framework that aligns with the vision and mission of LLDIKTI and demonstrates how each stakeholder's differences affect the use of information technology based on the maturity level of the implemented system. This research applied the COBIT 2019 framework in LLDIKTI Region II, utilizing the APO07, BAI08, and MEA03 domains. The results indicate that SIKITO's maturity level is below the expected value of -2.33, indicating a need for further development. This research contributes to the field by providing insights into the importance of aligning IT governance with an organization's vision and mission, and the role of maturity frameworks such as COBIT 2019 in achieving this alignment.